(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This prospective observational study compared the diagnostic accuracy of cystatin C-based and creatinine-based glomerular filtration rate equations in 112 children aged 3-15 years with stages 1-3 chronic kidney disease. Cystatin C-based estimation achieved significantly higher sensitivity for early renal decline. The combined creatinine-cystatin C equation demonstrated the best accuracy overall, supporting its routine adoption in pediatric nephrology practice.